The Scale Validation Of Amanah Ikhtiar Malaysia’s Microfinance Services And Household Socioeconomic Instrument: An Exploratory Factor Analysis - W Muhammad ZainuddinWan Abdullah; Hafiz Muhammad Zia Ul-Haq; W Nur Rahini AznieZainuddin (Penerbit USIM, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 21 Issue 2 Page (162-183)